Instructional Engineering in Science Education: A Systematic Literature Review of SDG-Oriented Project-Based Learning (2020–2025) - Sri Cahya Purnamasari; Laifa Rahmawati (Assyfa Learning Journal, 2026)
Background: Modern ecosystems demand the transformation of subject-specific knowledge into actionable instructional designs that foster 21st-century competencies and global sustainability. However, systematic integration of global standards into classroom methodologies remains inadequately mapped. Objective: This study aims to evaluate the strategic implementation of the Project-Based Learning (PjBL) model within science education to structurally support the United Nations' Sustainable Development Goals (SDGs). Method: Employing a Systematic Literature Review (SLR) guided by PRISMA protocols, 15 high-quality primary research articles from 2020 to 2025 were regularly selected and scrutinized from Google Scholar and Scopus databases after screening an initial pool of 770 documents. Results: The findings reveal a prominent upward trend in instructional modernization combining PjBL with STEM, STEAM, and digital frameworks. While current instructional strategies focus heavily on SDG 4 (Quality Education) and SDG 13 (Climate Action) to enhance students' scientific reasoning, environmental awareness, and creativity, substantial instructional design gaps persist for other core areas such as SDG 3, 7, and 12. Conclusion: This review highlights that embedding sustainable trajectories within PjBL frameworks successfully bridges the gap between disciplinary expert content and professional competency alignment, although future instructional designs must expand toward underexplored goals